Head and neck lymphomas: Review of 151 cases - Chao-Yin Kuo; Cheng-Ping Shih; Li-Hsiang Cheng; Shao-Cheng Liu; Feng-Hsiang Chiu; Yuan-Yung Lin; Je-Ming Hu; Yueng-Hsiang Chu (Journal of Medical Sciences, 2020)
Aim: Treatment of lymphoma differs from head and neck carcinomas. The aim of this study was to provide a comprehensive of review lymphomas arising in head and neck region. Methods: Patients between 2003 and 2015 with lymphomas in head and neck region were retrospectively reviewed with pathology subtype, age, gender, location, and diagnostic procedure. Results: One hundred and fifty-one lymphoma patients were enrolled. Diffuse large B-cell lymphoma accounted for 56.3% of all patients, followed by follicular lymphoma (6.0%) and NK/T-cell lymphoma (6.0%). Nearly 38.4% of patients manifested as enlarged cervical node while another 61.6% presented as extranodal lymphoma with tonsils (21.8%) the most commonly affected site, followed by parotid gland and tongue base. Open surgery or excisional biopsy had the highest sensitivity of 95.8% for a confirmed diagnosis, followed by punch biopsy (74.7%), core biopsy (51.0%), and fine-needle aspiration (2.2%). Conclusions: Lymphoma is frequently encountered in head and neck region. Early diagnosis was made possible by detailed examinations and adequate diagnostic procedure with consideration of both procedure sensitivity and risks.